2020
DOI: 10.1002/ajmg.a.62019
|View full text |Cite
|
Sign up to set email alerts
|

A pilot clinical trial with losartan in Myhre syndrome

Abstract: Introduction Myhre syndrome (MS) is an ultra‐rare disorder due to pathogenic variants in the SMAD4 gene that encodes a protein regulating the TGF‐β pathway and extra‐cellular matrix (ECM) homeostasis. Main clinical features of MS include thickening of skin and joint stiffness. Previous studies showed that losartan improved ECM deposition in MS fibroblasts. Materials and methods Four molecularly confirmed MS subjects (mean age 23.8 ± 17 years) were evaluated for: (a) skin thickness by Rodnan score, (b) joint ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Recently, Cappuccio et al, lead a pilot clinical trial with losartan on four MS patients and identified clinical endpoints on skin thickness, joints range of motion and speckle-tracking echocardiogram of left ventricular function to evaluate losartan efficacy. Authors suggested that losartan might provide benefit to patient with improvements in skin thickness, joint range of motion and to a lesser extent of myocardial strain in MS [ 41 ]. The natural history of MS provided by our study highlighted the occurrence of life-threatening complications such as vascular stenosis or PH.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Cappuccio et al, lead a pilot clinical trial with losartan on four MS patients and identified clinical endpoints on skin thickness, joints range of motion and speckle-tracking echocardiogram of left ventricular function to evaluate losartan efficacy. Authors suggested that losartan might provide benefit to patient with improvements in skin thickness, joint range of motion and to a lesser extent of myocardial strain in MS [ 41 ]. The natural history of MS provided by our study highlighted the occurrence of life-threatening complications such as vascular stenosis or PH.…”
Section: Discussionmentioning
confidence: 99%
“…A second cardiac surgery was performed at 2 years of age for correction of the left pulmonary artery. She has been on furosemide and losartan treatment (Cappuccio et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…A second cardiac surgery was performed at 2 years of age for correction of the left pulmonary artery. She has been on furosemide and losartan treatment(Cappuccio et al, 2021).At the age of 2.8 years, the echocardiogram and cardiac catheterization showed moderate RV outflow tract obstruction (right pulmonary artery 6 mm, left pulmonary artery 5 mm, transpulmonary pressure gradient 65 mmHg), pulmonary valve annulus diameter 7 mm (Z score À3.38). Severe tricuspid valve regurgitation with tricuspid annular plane systolic excursion 7-8 mm was diagnosed.…”
mentioning
confidence: 99%
“…Myhre syndrome (MS) is driven by pathogenic variants of Smad4 gene. Losartan improves skin thickness and joint range motion in MS [132]. The beneficial role of losartan in Smad4-deficient diseases like MS suggests that losartan may indirectly remediate aberrant Smad4.…”
Section: Smad4mentioning
confidence: 98%